Teknik Pengolahan Duck Confit di Hot Kitchen Pada Finns VIP Beach Club Canggu Bali - Ni Kadek Indah Rohani; Sutapa, I Ketut; Agung Rai Antara, I Made (HARMONY HOSPITALITY, 2024)
This study aims to find out the duck confit processing technique, the obstacles faced in the duck confit processing technique and the efforts made to overcome the obstacles in the duck confit processing technique in the hot kitchen at Finns VIP Beach Club Canggu Bali. The data collection method was carried out by conducting observations, interviews, and documentation using qualitative descriptive analysis techniques, namely explaining and describing duck confit processing techniques in the hot kitchen at Finns VIP Beach Club Canggu Bali. The obstacles faced in the duck confit processing technique in the hot kitchen at Finns VIP Beach Club Canggu Bali are in the selection of basic ingredients, especially duck, storing duck confit, cooking time and maintaining the consistency of the dish. The business effort carried out is to use imported duck and use adequate tools such as vacuum machines to store it and convothem to cook duck confit. The results of the study showed that there were obstacles in the processing of duck confit, namely in the cooking process and lack of precision in processing duck confit. The suggestion is to immediately realize what has been conveyed by the speakers.